2005
DOI: 10.2337/diabetes.54.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Induces Monocytic Release of Interleukin-6 via Induction of Protein Kinase C-α and -β

Abstract: Diabetes confers an increased propensity to atherosclerosis. Inflammation is pivotal in atherogenesis, and diabetes is a proinflammatory state. Interleukin (IL)-6, in addition to inducing the acute-phase response, contributes to insulin resistance. Monocytes from type 2 diabetic patients secrete increased IL-6. The aim of this study was to examine molecular mechanisms for increased IL-6 release from monocytes under hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(145 citation statements)
references
References 33 publications
5
136
1
3
Order By: Relevance
“…In a laboratory study, monocytic cells were cultured in the presence of 5.5 mmol/l (normal) or 15 mmol/l (high) glucose and mannitol. Secreted IL-6, intracellular IL-6, and IL-6 mRNA were found to be significantly increased with hyperglycemia (P < 0.001) [48]. In addition, Qi and colleagues found that diets high in fiber may increase plasma adiponectin concentrations in diabetic patients [49] and adiponectin has been found to have profound anti-inflammatory effects [50].…”
Section: Discussionmentioning
confidence: 99%
“…In a laboratory study, monocytic cells were cultured in the presence of 5.5 mmol/l (normal) or 15 mmol/l (high) glucose and mannitol. Secreted IL-6, intracellular IL-6, and IL-6 mRNA were found to be significantly increased with hyperglycemia (P < 0.001) [48]. In addition, Qi and colleagues found that diets high in fiber may increase plasma adiponectin concentrations in diabetic patients [49] and adiponectin has been found to have profound anti-inflammatory effects [50].…”
Section: Discussionmentioning
confidence: 99%
“…DAG have been implicated in the development of IR via activation of specific protein kinase C (PKC) isoforms [5]. PKC is known to induce IL-6 synthesis [14]. However, ceramides seemed to be more strongly associated with IL-6 levels than DAG, independently of the degree of IR as assessed by HOMA-IR index.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies suggest that glucose-induced superoxide formation stems from glucose-6-phosphate dehydrogenase and phosphokinase C-dependent activation of NAD(P)H oxidase [7]. Subsequently, the production of pro-inflammatory immune mediators occurs via the activation of mitogen-activated kinases p38 and Jun N-terminal kinase (JNK), other tyrosine kinases, transcription factors such as transcription factor activator protein-1 (AP-1) and nuclear factor κB (NFκB), and/or poly(ADPribose) polymerase [8,9].…”
Section: Introductionmentioning
confidence: 99%